2020
DOI: 10.3390/ph13040053
|View full text |Cite
|
Sign up to set email alerts
|

Study of In Vitro and In Vivo Carbamazepine Release from Coarse and Nanometric Pharmaceutical Emulsions Obtained via Ultra-High-Pressure Homogenization

Abstract: In the past decade, pharmaceutical nanotechnology has proven to be a promising alternative for improving the physicochemical and biopharmaceutical features for conventional pharmaceutical drug formulations. The goal of this study was to develop, characterize, and evaluate the in vitro and in vivo release of the model drug carbamazepine (CBZ) from two emulsified formulations with different droplet sizes (coarse and nanometric). Briefly, oil-in-water emulsions were developed using (i) Sacha inchi oil, ultrapure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…One of commonly used variants of this method is a two-stage technology that combines precipitation with high-pressure homogenization. This method has been successfully used to form nanocrystals of drugs such as Albendazole [31], Carbamazepine [32], and Amphotherin B [33]. Nanosuspensions of Aprepitant and Ibuprofen have also been produced [34] using a combination of pretreatment methods, including precipitation and ball milling followed by high-pressure homogenization, resulting in nanoparticles of about 100 nm in size.…”
Section: High-pressure Homogenizationmentioning
confidence: 99%
“…One of commonly used variants of this method is a two-stage technology that combines precipitation with high-pressure homogenization. This method has been successfully used to form nanocrystals of drugs such as Albendazole [31], Carbamazepine [32], and Amphotherin B [33]. Nanosuspensions of Aprepitant and Ibuprofen have also been produced [34] using a combination of pretreatment methods, including precipitation and ball milling followed by high-pressure homogenization, resulting in nanoparticles of about 100 nm in size.…”
Section: High-pressure Homogenizationmentioning
confidence: 99%
“…Echeverri et al synthesized nanoemulsions loaded with carbamazepine drug via ultra-highpressure homogenization [43]. Experiments on rats indicated that the nanoemulsions significantly improved the drug absorption time in blood, from 12 hours for coarse emulsion to 45 minutes for nanoemulsion formulations.…”
Section: Rhamnolipid-coatedmentioning
confidence: 99%
“…The use of ALA for the preparation of a nanoemulsion was investigated by Kuznetcova et al, who obtained a stable formulation of about 100 nm with a negative surface charge [11]. Moreover, sacha inchi oil was exploited by Echeverri et al to prepare a nanoemulsion with good stability over time, unlike the coarse emulsion [46].…”
Section: Nanoemulsion Systemsmentioning
confidence: 99%